Glass composition, glass product, display device, and electronic device
By using a glass composition with a specific composition and strengthening treatment, glass products suitable for foldable electronic devices are prepared, which solves the problems of crease generation and insufficient impact resistance during folding, and realizes thin and durable glass products.
Patent Information
- Application Number
- CN202510333991.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-22
- Filing Date
- 2025-03-20
- Publication Date
- 2025-09-23
AI Technical Summary
Existing glass products are prone to creases during repeated folding in foldable electronic devices, and it is difficult to simultaneously have sufficient impact resistance and thinness to meet the requirements of portable electronic devices.
A glass composition with a specific composition, including SiO2, Al2O3, Na2O, Li2O and MgO, whose proportions satisfy a certain relationship, is used to prepare glass products with appropriate thickness and elastic modulus, meeting the requirements of foldability and impact resistance, and improving the mechanical properties of the glass through strengthening treatment.
While reducing the generation of creases during the folding process, it also improves the impact resistance and mechanical strength of glass products, making it suitable for thin and durable foldable electronic devices.
Smart Images

Figure CN120681957A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2024-0039982, filed on March 22, 2024, in the Korean Intellectual Property Office (KIPO), the entire contents of which are incorporated herein by reference. Technical Field
[0003] One or more embodiments relate to a glass composition, a glass product prepared from the glass composition, a display device, and an electronic device. Background Art
[0004] Glass products are widely used in electronic devices including display panels or as building materials. For example, glass products are applied to substrates of flat panel display panels such as liquid crystal display (LCD) panels, organic light emitting display (OLED) panels, or electrophoretic display panels, or to cover windows for protecting them.
[0005] As portable electronic devices such as smartphones and tablet personal computers (PCs) become popular, glass products used therefor are frequently exposed to external impacts. For portability, there is a demand for glass products that are thin but can withstand external impacts.
[0006] Recently, research has been conducted on foldable electronic devices including display panels for user convenience. It is desirable that glass products used in foldable electronic devices have a small thickness and sufficient strength to withstand external impact, thereby alleviating bending stress when the glass product is folded. Furthermore, when foldable electronic devices are repeatedly folded, it is desirable to reduce creases that may form during the repeated folding operations. Summary of the Invention
[0007] One or more embodiments provide a glass composition in which impact resistance is improved while reducing the generation of creases in the glass folding area, a glass product prepared from the glass composition, a display device, and an electronic device. However, this is merely an example, and the scope of the present disclosure is not limited thereto.
[0008] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the disclosed embodiments.
[0009] According to embodiments, a glass article may include a glass composition comprising, relative to the total weight of the glass composition, SiO2 in a range of about 60 mol% to about 70 mol%, Al2O3 in a range of about 5 mol% to about 15 mol%, Na2O in a range of about 5 mol% to about 15 mol%, Li2O in a range of about 5 mol% to about 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to about 5 mol%. The glass composition may satisfy Relationship 1, and the glass article may have a thickness in a range of about 20 μm to about 100 μm.
[0010] [Equation 1]
[0011] 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0
[0012] In Relationship Formula 1, Al2O3, Na2O, and Li2O may represent the content of each component in mol%.
[0013] The glass article may have an elastic modulus in a range from about 75 GPa to about 85 GPa.
[0014] The brittleness of glass products can be around 4.9μm -0.5 to about 5.6 μm -0.5 within the range.
[0015] The thermal expansion coefficient of glass products can be about 85*10 -7 K -1 To about 120*10 -7 K -1 within the range.
[0016] The glass transition temperature of the glass article may be in the range of about 425°C to about 525°C.
[0017] The density of glass products can be about 2.38g / cm 3 to about 2.48g / cm 3 within the range.
[0018] The glass article may have a Poisson's ratio in the range of about 0.20 to about 0.28.
[0019] The glass article may have a Vickers hardness in the range of about 5.50 GPa to about 6.50 GPa.
[0020] The fracture toughness of glass products can be around 0.75MPa*m 0.5 to about 0.85MPa*m 0.5 within the range.
[0021] The glass article may be foldable.
[0022] The glass composition may also satisfy Relationship 2.
[0023] [Equation 2]
[0024] 0.3≤Al2O3 / (the sum of Na2O, Li2O and MgO)≤1.0
[0025] In Relational Formula 2, Al2O3, Na2O, Li2O, and MgO may represent the content of each component in mol%.
[0026] According to an embodiment, the glass composition may include SiO2 in a range of about 60 mol% to about 70 mol%, Al2O3 in a range of about 5 mol% to about 15 mol%, Na2O in a range of about 5 mol% to about 15 mol%, Li2O in a range of about 5 mol% to about 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to about 5 mol%, relative to the total weight of the glass composition. The glass composition may satisfy Relationship 1.
[0027] [Equation 1]
[0028] 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0
[0029] In Relationship Formula 1, Al2O3, Na2O, and Li2O may represent the content of each component in mol%.
[0030] According to an embodiment, a display device may include a display panel including a plurality of pixels and a cover window disposed on the display panel. The cover window may include, as a glass composition, SiO2 in a range of about 60 mol% to about 70 mol%, Al2O3 in a range of about 5 mol% to about 15 mol%, Na2O in a range of about 5 mol% to about 15 mol%, Li2O in a range of about 5 mol% to about 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to about 5 mol%, relative to the total weight of the cover window. The glass composition may satisfy Relationship 1, and the cover window may have a thickness in a range of about 20 μm to about 100 μm.
[0031] [Equation 1]
[0032] 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0
[0033] In Relationship Formula 1, Al2O3, Na2O, and Li2O may represent the content of each component in mol%.
[0034] The elastic modulus of the cover window may be in a range from about 75 GPa to about 85 GPa.
[0035] The brittleness of the cover window can be around 4.9 μm -0.5 to about 5.6 μm -0.5 within the range.
[0036] The thermal expansion coefficient of the cover window can be about 85*10 -7 K -1 To about 120*10 -7 K -1 within the range.
[0037] The glass transition temperature of the cover window may be in the range of about 425°C to about 525°C.
[0038] The density of the cover window can be about 2.38g / cm 3 to about 2.48g / cm 3 within the range.
[0039] The Poisson's ratio of the cover window may be in the range of about 0.20 to about 0.28.
[0040] The Vickers hardness of the cover window may be in the range of about 5.50 GPa to about 6.50 GPa.
[0041] The fracture toughness of the cover window can be around 0.75MPa*m 0.5 to about 0.85MPa*m 0.5 within the range.
[0042] According to an embodiment, an electronic device may include a display panel including a plurality of pixels and a cover window disposed on the display panel. The cover window may include, as a glass composition, SiO2 in a range of about 60 mol% to about 70 mol%, Al2O3 in a range of about 5 mol% to about 15 mol%, Na2O in a range of about 5 mol% to about 15 mol%, Li2O in a range of about 5 mol% to about 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to about 5 mol%, relative to the total weight of the cover window. The glass composition may satisfy Relationship 1, and the cover window may have a thickness in a range of about 20 μm to about 100 μm.
[0043] [Equation 1]
[0044] 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0
[0045] In Relationship Formula 1, Al2O3, Na2O, and Li2O may represent the content of each component in mol%. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The above and other aspects, features and advantages of the embodiments of the present disclosure will become more apparent from the following description made in conjunction with the accompanying drawings, in which:
[0047] Figure 1A 、 Figure 1B 、 Figure 1C and Figure 1D each is a perspective view of a glass article according to an embodiment;
[0048] Figure 2 and Figure 3 is a schematic perspective view of an electronic device to which a glass article is applied according to an embodiment;
[0049] Figure 4 is a schematic cross-sectional view of a portion of an electronic device according to an embodiment;
[0050] Figure 5 is a schematic cross-sectional view of a glass article according to an embodiment; and
[0051] Figure 6 is a graph showing stress distribution of a glass article according to an embodiment. DETAILED DESCRIPTION
[0052] Reference will now be made in detail to embodiments, examples of which are illustrated in the accompanying drawings, wherein like reference numerals refer to like elements throughout. In this regard, the embodiments may have different forms and should not be construed as limited to the descriptions set forth herein. Therefore, the embodiments are described below with reference to the drawings only to explain various aspects of the present description.
[0053] Because the present disclosure allows for various variations and numerous embodiments, specific embodiments will be illustrated in the drawings and described in detail in the written description. Reference is made to the drawings illustrating embodiments of the present disclosure in order to gain a full understanding of the present disclosure, its advantages, and the objectives achieved by its implementation. However, the present disclosure can be implemented in many different forms and should not be construed as limited to the embodiments set forth herein.
[0054] It will be understood that although the terms “first,” “second,” etc. may be used herein to describe various elements, these elements should not be limited by these terms and these terms are only used to distinguish one element from another.
[0055] As used herein, the singular forms "a," "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0056] It will also be understood that the terms “comprises” and / or “comprising” as used herein specify the presence of stated features or components, but do not preclude the presence or addition of one or more other features or components.
[0057] For the convenience of explanation, the size of the elements in the drawings may be exaggerated. In other words, since the size and thickness of the elements in the drawings are arbitrarily shown for the convenience of explanation, the following embodiments are not limited thereto.
[0058] Throughout the specification and claims, for purposes of its meaning and interpretation, the phrase "at least one of" is intended to include the meaning of "at least one selected from the group of." For example, "at least one of A and B" may be understood to mean "A, B, or A and B." Throughout the specification and claims, for purposes of its meaning and interpretation, the term "and / or" is intended to include any combination of the terms "and" and "or." For example, "A and / or B" may be understood to mean "A, B, or A and B." The terms "and" and "or" may be used in conjunction or disjunction and may be understood to be equivalent to "and / or."
[0059] When an element or layer is referred to as being "on," "connected to," or "coupled to" another element or layer, it may be directly on, directly connected to, or directly coupled to the other element or layer, or there may be intervening elements or layers. However, when an element or layer is referred to as being "directly on," "directly connected to," or "directly coupled to" another element or layer, there may be no intervening elements or layers. For this purpose, the term "connected" may refer to a physical, electrical, and / or fluid connection with or without intervening elements. Furthermore, when an element is referred to as being "in contact with," "touching," etc., another element, it may be in "electrical contact" or "physical contact" with the other element; or in "indirect contact" or "direct contact" with the other element.
[0060] In the following examples, the x-axis, y-axis, and z-axis are not limited to the three axes of the rectangular coordinate system and can be interpreted in a broader sense. For example, the x-axis, y-axis, and z-axis can be perpendicular to each other, or can represent different directions that are not perpendicular to each other.
[0061] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art, taking into account the errors associated with the measurements and the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, ±5% of the stated value.
[0062] Unless otherwise defined or implied herein, all terms (including technical and scientific terms) used have the same meaning as commonly understood by those skilled in the art to which the present disclosure belongs. It should also be understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an idealized or overly rigid sense unless explicitly defined in the specification.
[0063] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent the same elements, and repeated descriptions thereof will be omitted.
[0064] Glass is used in electronic devices (e.g., tablet personal computers (PCs), notebook computers, smartphones, e-books, televisions (TVs), PC monitors), refrigerators and washing machines equipped with displays, as cover windows for display panels, substrates for touch panels, and optical components such as light guides. Glass is also used in vehicle applications, such as cover glass for dashboards, cover glass for solar cells, architectural interior materials, and windows for buildings or homes.
[0065] Such glass needs to have great strength. For example, it is desirable that glass used for windows be thin to meet requirements such as high transmittance and lightness, while also being strong enough to resist breakage from external impact. Glass with increased strength can be manufactured using various methods, such as chemical or thermal strengthening. Figures 1A to 1D Embodiments of glass articles having various shapes are shown.
[0066] like Figure 1A As shown in , in an embodiment, the glass article 1000a can be a flat sheet or a flat plate. In another embodiment, as Figure 1B 、 Figure 1C and Figure 1D As shown in FIG, glass articles 1000b, 1000c, and 1000d may have a three-dimensional shape including a curved portion. Figure 1B As shown in FIG, the glass article 1000b may have a flat portion with a bent edge. Figure 1C As shown in FIG, the glass article 1000c can be substantially curved. For example, as shown in FIG. Figure 1D As shown in FIG, the glass article 1000d can be folded. In another embodiment, the glass article 1000a can be a foldable glass article formed into a flat sheet or a flat plate and foldable or bendable due to its flexibility. In another embodiment, the glass article 1000a can be stretchable or rollable.
[0067] The glass articles 1000a to 1000d may have a rectangular planar shape, but the present disclosure is not limited thereto. The shape may vary; for example, the glass articles 1000a to 1000d may have a rectangular, square, circular, or elliptical planar shape with rounded edges. In the following embodiments, the glass articles 1000a to 1000d are described as rectangular flat plates, but the present disclosure is not limited thereto.
[0068] Figure 2 and Figure 3 1 is a schematic perspective view of an electronic device 1 to which a glass product is applied according to an embodiment. Figure 2 The electronic device 1 is shown in an unfolded state, and Figure 3 The electronic device 1 is shown in a folded state.
[0069] Reference Figure 2 and Figure 3 The electronic device 1 may include a lower cover LC, a display panel DP, and a cover window CW. The electronic device 1 may include a display device. The display device may include a display panel DP and a cover window CW. The electronic device 1 according to the embodiment may be a foldable electronic device. The cover window CW may be a reference Figures 1A to 1D The glass product is described, and the glass product can be folded due to its flexibility.
[0070] The lower cover LC may include a first portion P1 and a second portion P2 supporting the display panel DP. The lower cover LC may be foldable about a folding axis FAX defined between the first portion P1 and the second portion P2. In an embodiment, the lower cover LC may further include a hinge portion HP, and the hinge portion HP may be disposed between the first portion P1 and the second portion P2.
[0071] The display panel DP may provide an image IMAGE, and includes a display area DA and a peripheral area PA adjacent to the display area DA.
[0072] In the display area DA, a plurality of pixels PX may be arranged, and an image IMAGE may be provided by the array of pixels PX. Each pixel PX may be defined as an emission area where light is emitted from a light-emitting element electrically connected to a pixel circuit. In an embodiment, each pixel PX may emit red light, green light, or blue light. In another embodiment, each pixel PX may emit red light, green light, blue light, or white light.
[0073] The peripheral area PA may be a non-display area that does not provide an image, and in the peripheral area PA, various lines, driving circuits, etc. may be arranged to provide electrical signals or power to the display area DA.
[0074] The light-emitting elements included in the display panel DP may include organic light-emitting diodes, inorganic light-emitting diodes, micro light-emitting diodes, and / or quantum dot light-emitting diodes. Hereinafter, for convenience, an embodiment in which the light-emitting elements included in the display panel DP include organic light-emitting diodes is described, but the following description is not limited thereto. The display panel DP may include other types of light-emitting elements.
[0075] The display area DA may include a first display area DA1 and a second display area DA2 located on a side of the display area DA relative to a folding axis FAX intersecting the display area DA. In embodiments, the display area DA may include a folding area FDA located between the first display area DA1 and the second display area DA2. For example, the first display area DA1, the second display area DA2, and the folding area FDA may each provide independent images, or the first display area DA1, the second display area DA2, and the folding area FDA may provide an image as a whole.
[0076] The first display area DA1 and the second display area DA2 may overlap with the first portion P1 and the second portion P2 of the lower cover LC, respectively, in the thickness direction of the display panel DP. The folding area FDA may overlap with the hinge portion HP of the lower cover LC in the thickness direction. The display panel DP may be foldable about a folding axis FAX. The folding area FDA may bend as the display panel DP is folded. When the display panel DP is folded, the first display area DA1 may face the second display area DA2.
[0077] Figure 2 and Figure 3 The folding axis FAX is shown extending in the y direction, but the present disclosure is not limited thereto. In another embodiment, the folding axis FAX may extend in the x direction intersecting the y direction. In another embodiment, in the xy plane, the folding axis FAX may extend in a direction intersecting the x direction and the y direction.
[0078] Figure 2 and Figure 3 The electronic device 1 is shown to include one folding axis FAX, but the present disclosure is not limited thereto. In another embodiment, the display panel DP may include multiple folding axes FAX intersecting the display area DA and may be folded multiple times relative to the folding axis FAX.
[0079] The cover window CW may be arranged on the display panel DP and cover the display panel DP. The cover window CW may be foldable or bendable in response to an external impact without cracking. When the display panel DP is folded about the folding axis FAX, the cover window CW may also be folded.
[0080] In a plan view, the shape of the electronic device 1 may be substantially rectangular. Figure 2 As shown in FIG, the electronic device 1 may generally have a rectangular shape in a plan view including sides extending in a first direction (e.g., the x-direction) and sides extending in a second direction (e.g., the y-direction). In an embodiment, the corner where the side in the first direction and the side in the second direction of the electronic device 1 intersect may have a right angle shape or a rounded shape with a curvature. The planar shape of the electronic device 1 is not limited to a rectangle and may be changed. For example, the shape of the electronic device 1 may be a circle, an ellipse, a polygon such as a triangle, or an irregular shape.
[0081] The electronic device 1 may be a product from various product lines, for example, a portable electronic device (such as a mobile phone, a smart phone, a tablet PC, a mobile communication terminal, a personal digital assistant, an e-book terminal, a portable multimedia player (PMP), a navigation device, or an ultra-mobile PC (UMPC)), a TV, a notebook computer, a monitor, a billboard, an Internet of Things (IoT) device, etc.
[0082] Figure 4 is a schematic cross-sectional view of a portion of the electronic device 1 according to the embodiment. Figure 4 It is along Figure 2 Schematic cross-sectional view of the display panel DP and the cover window CW of the display device 1 taken along line II'.
[0083] Reference Figure 4 The display panel DP may include a stacked structure including a substrate 10, a pixel circuit layer PCL, a display element layer DEL, a thin film encapsulation layer TFE, a touch electrode layer TEL, and an optical function layer OFL.
[0084] The substrate 10 may include glass or a polymer resin. For example, the substrate 10 may include a polymer resin including polyethersulfone, polyarylate, polyetherimide, polyethylene naphthalate, polyethylene terephthalate, polyphenylene sulfide, polyimide, polycarbonate, cellulose triacetate, cellulose acetate propionate, and the like.
[0085] The pixel circuit layer PCL may be disposed on the substrate 10 . Figure 4 The pixel circuit layer PCL is shown to include a thin film transistor TFT, and a buffer layer 11 , a first insulating layer 13 a , a second insulating layer 13 b , a third insulating layer 15 , and a planarization layer 17 arranged below and / or above components of the thin film transistor TFT.
[0086] The buffer layer 11 may reduce or prevent the penetration of foreign matter, moisture, or external air from the bottom of the substrate 10 and provide a flat surface on the substrate 10. The buffer layer 11 may include an inorganic insulating material such as silicon nitride (SiN x), silicon oxynitride (SiON) and silicon oxide (SiO2), and may be one or more layers including an inorganic insulating material.
[0087] The thin film transistor (TFT) on the buffer layer 11 may include a semiconductor layer 12, and the semiconductor layer 12 may include polycrystalline silicon. In another embodiment, the semiconductor layer 12 may include amorphous silicon, an oxide semiconductor, an organic semiconductor, or the like. The semiconductor layer 12 may include a channel region 12c and a drain region 12a and a source region 12b, respectively disposed on either side of the channel region 12c. The gate electrode 14 may overlap the channel region 12c in the thickness direction.
[0088] The gate electrode 14 may include a low-resistance metal material, a conductive material such as molybdenum (Mo), aluminum (Al), copper (Cu), or titanium (Ti), and may be one or more layers including the above materials.
[0089] The first insulating layer 13a may be disposed between the semiconductor layer 12 and the gate electrode 14. The first insulating layer 13a may include an inorganic insulating material such as SiO2, SiN x , SiON, aluminum oxide (Al2O3), titanium oxide (TiO2), tantalum oxide (Ta2O5), hafnium oxide (HfO2) or zinc oxide (ZnO x ). Zinc oxide (ZnO x ) may be ZnO and / or ZnO2.
[0090] The second insulating layer 13b may cover the gate electrode 14. The second insulating layer 13b may include an inorganic insulating material such as SiO2, SiN x , SiON, Al2O3, TiO2, Ta2O5, HfO2 or ZnO x .
[0091] The upper electrode Cst2 of the storage capacitor Cst can be arranged on the second insulating layer 13b. The upper electrode Cst2 can at least partially overlap with the gate electrode 14 in the thickness direction. The gate electrode 14 and the upper electrode Cst2 overlapping each other with the second insulating layer 13b interposed therebetween can form the storage capacitor Cst. For example, the gate electrode 14 can function as the lower electrode Cst1 of the storage capacitor Cst.
[0092] As described, the storage capacitor Cst may overlap with the thin film transistor TFT in the thickness direction. In another embodiment, the storage capacitor Cst may not overlap with the thin film transistor TFT. For example, as a component separate from the gate electrode 14, the lower electrode Cst1 of the storage capacitor Cst may be formed separately from the gate electrode 14.
[0093] The upper electrode Cst2 may include Al, platinum (Pt), palladium (Pd), silver (Ag), magnesium (Mg), gold (Au), nickel (Ni), neodymium (Nd), iridium (Ir), chromium (Cr), calcium (Ca), Mo, Ti, tungsten (W) and / or Cu, and may be one or more layers including the above materials.
[0094] The third insulating layer 15 may cover the upper electrode Cst2. The third insulating layer 15 may include SiO2, SiN x , SiON, Al2O3, TiO2, Ta2O5, HfO2, ZnO x The third insulating layer 15 may be one or more layers including the above inorganic insulating materials.
[0095] The drain electrode 16a and the source electrode 16b may each be arranged on the third insulating layer 15. The drain electrode 16a and the source electrode 16b may be connected to the drain region 12a and the source region 12b, respectively, through contact holes formed in the insulating layer below the drain electrode 16a and the source electrode 16b. The drain electrode 16a and the source electrode 16b may each include a material having good electrical conductivity. The drain electrode 16a and the source electrode 16b may each include a conductive material such as Mo, Al, Cu or Ti, and may be one or more layers including the above materials. In an embodiment, the drain electrode 16a and the source electrode 16b may have a multilayer structure of Ti / Al / Ti.
[0096] The planarization layer 17 may include an organic insulating layer. The planarization layer 17 may include an organic insulating material, such as a general polymer (such as polymethyl methacrylate (PMMA) or polystyrene (PS)), a polymer derivative having a phenolic group, an acrylic polymer, an imide polymer, an aryl ether polymer, an amide polymer, a fluorine polymer, a p-xylene polymer, a vinyl alcohol polymer, and a blend thereof.
[0097] The display element layer DEL may be disposed above the pixel circuit layer PCL having the above-described structure. The display element layer DEL may include an organic light-emitting diode OLED as a light-emitting element, and the organic light-emitting diode OLED may have a stacked structure including a first electrode 21, an emission layer 22, and a second electrode 23. The first electrode 21 of the organic light-emitting diode OLED may be electrically connected to the thin film transistor TFT through a contact hole defined in the planarization layer 17.
[0098] The first electrode 21 may include a conductive oxide such as indium tin oxide (ITO), indium zinc oxide (IZO), ZnO, indium oxide (In2O3), indium gallium oxide (IGO), or aluminum zinc oxide (AZO). In an embodiment, the first electrode 21 may include a reflective layer containing Ag, Mg, Al, Pt, Pd, Au, Ni, Nd, Ir, Cr, or compounds thereof. In an embodiment, the first electrode 21 may further include a layer containing ITO, IZO, ZnO, or In2O3 above or below the above reflective layer.
[0099] A pixel defining layer 19 including an opening 19OP exposing at least a portion of the first electrode 21 may be disposed on the first electrode 21. The pixel defining layer 19 may include an organic insulating material and / or an inorganic insulating material. The opening 19OP may define an emission region for light emitted from the organic light emitting diode OLED. For example, the size / width of the opening 19OP may correspond to the size / width of the emission region. Therefore, the size and / or width of the pixel PX may depend on the size and / or width of the opening 19OP of the pixel defining layer 19.
[0100] The emission layer 22 may be disposed in the opening 19OP of the pixel defining layer 19. The emission layer 22 may include a high molecular weight or low molecular weight organic material that emits light of one color. In another embodiment, the emission layer 22 may include an inorganic emission material or quantum dots.
[0101] although Figure 4 Although not shown in the figure, a first functional layer and a second functional layer may be arranged below the emission layer 22 and on the emission layer 22, respectively. The first functional layer may include, for example, a hole transport layer (HTL) or both an HTL and a hole injection layer (HIL). The second functional layer may include an electron transport layer (ETL) and / or an electron injection layer (EIL). However, the present disclosure is not limited thereto. The first functional layer and the second functional layer may be selectively arranged on and below the emission layer 22, respectively. Similar to the second electrode 23 described below, the first functional layer and / or the second functional layer may each be a common layer formed to completely cover the substrate 10.
[0102] The second electrode 23 may be located on the first electrode 21 and overlap with the first electrode 21 in the thickness direction. The second electrode 23 may include a conductive material having a low work function. For example, the second electrode 23 may include a transparent (or translucent) layer containing Ag, Mg, Al, Pt, Pd, Au, Ni, Nd, Ir, Cr, Li, Ca or an alloy thereof. In an embodiment, the second electrode 23 may also include a layer including ITO, IZO, ZnO or In2O3 on the transparent (or translucent) layer including the above materials. The second electrode 23 may be formed integrally to completely cover the substrate 10.
[0103] The encapsulation member may be arranged on top of the display element layer DEL. In an embodiment, the encapsulation member may be prepared as a thin film encapsulation layer TFE. The thin film encapsulation layer TFE may be arranged on and cover the display element layer DEL. The thin film encapsulation layer TFE may include at least one inorganic encapsulation layer and at least one organic encapsulation layer. In an embodiment, the thin film encapsulation layer TFE may include a first inorganic encapsulation layer 31, an organic encapsulation layer 32, and a second inorganic encapsulation layer 33 stacked sequentially. In another embodiment, the encapsulation member may be prepared as an encapsulation substrate.
[0104] The first inorganic encapsulation layer 31 and the second inorganic encapsulation layer 33 may each include Al2O3, TiO2, Ta2O5, HfO2, ZnO, SiO2, SiN x and SiON. The organic encapsulation layer 32 may include a polymer-based material. The polymer-based material may include acrylic resin, epoxy resin, polyimide, polyethylene, etc. In an embodiment, the organic encapsulation layer 32 may include acrylate. The organic encapsulation layer 32 may be formed by curing a monomer or applying a polymer.
[0105] A touch electrode layer TEL including touch electrodes may be disposed on the thin film encapsulation layer TFE, and an optical function layer OFL may be disposed on the touch electrode layer TEL. The touch electrode layer TEL may obtain coordinate information based on external input (e.g., a touch event). The optical function layer OFL may reduce the reflectivity of light (external light) incident on the electronic device 1 from the outside and / or may improve the color purity of light emitted from the electronic device 1.
[0106] In embodiments, the optical functional layer OFL may include a retarder and / or a polarizer. The retarder may be a film-type or liquid crystal coating-type, and may include a λ / 2 retarder and / or a λ / 4 retarder. The polarizer may also be a film-type or liquid crystal coating-type. The film-type may include a stretched synthetic resin film, and the liquid crystal coating-type may include liquid crystals arranged in a specific arrangement. The retarder and polarizer may further include a protective film.
[0107] In an embodiment, the optical function layer OFL may include a destructive interference structure. The destructive interference structure may include a first reflective layer and a second reflective layer arranged at different layers. The first reflected light and the second reflected light reflected from the first reflective layer and the second reflective layer, respectively, may destructively interfere with each other, and the reflectivity of the external light may be reduced accordingly.
[0108] An adhesive member may be disposed between the touch electrode layer TEL and the optical function layer OFL. Conventional adhesive members may be used without limitation. For example, the adhesive member may be a pressure sensitive adhesive (PSA).
[0109] The cover window CW may be disposed above the display panel DP and may be attached to the display panel DP by an adhesive member.
[0110] The cover window CW may have high transmittance to transmit light emitted from the display panel DP. In an embodiment, the transmittance of the cover window CW may be at least about 85%, and the haze of the cover window CW may be less than or equal to about 2%, but the present disclosure is not limited thereto.
[0111] In an embodiment, the cover window CW may have a small thickness to reduce the weight of the electronic device 1 , and have great strength and hardness to protect the display panel DP from external impact.
[0112] Figure 5 The above reference Figure 1A A schematic cross-sectional view of the flat plate-shaped glass product 1000a.
[0113] Reference Figure 5 The glass article 1000a may include a first surface S1, a second surface S2, and side surfaces. In the glass article 1000a having a flat plate shape, the first surface S1 and the second surface S2 may be main surfaces having large areas, and the side surfaces may be outer surfaces connecting the first surface S1 to the second surface S2.
[0114] The first surface S1 and the second surface S2 may face each other in the thickness direction (eg, z direction). Figure 2 and Figure 4 In the case where the cover window CW of the electronic device 1 transmits light, light may be mainly introduced through one of the first surface S1 and the second surface S2 and pass through the other of the first surface S1 and the second surface S2.
[0115] The thickness t of the glass article 1000a can be defined as the distance between the first surface S1 and the second surface S2. The thickness t of the glass article 1000a is not limited thereto, but may be less than or equal to approximately 100 μm. For example, the thickness t of the glass article 1000a may be within a range of approximately 20 μm to approximately 100 μm. In an embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 80 μm. In another embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 75 μm. In another embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 70 μm. In another embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 60 μm. In another embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 65 μm. In another embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 50 μm. In another embodiment, the thickness t of the glass article 1000a may be less than or equal to approximately 30 μm. In an embodiment, the thickness t of the glass article 1000a may be in a range of about 20 μm to about 50 μm. For example, the thickness t of the glass article 1000a may be about 30 μm. The glass article 1000a may have a uniform thickness t, but the present disclosure is not limited thereto. The glass article 1000a may have different thicknesses t in different portions.
[0116] The glass article 1000a can be strengthened and have a specific stress distribution within the glass article 1000a. Compared to the glass article 1000a before strengthening, the strengthened glass article 1000a can better prevent crack formation, crack propagation, breakage, etc. caused by external impact. The glass article 1000a strengthened by the strengthening process can have various stresses specific to each portion. For example, compression regions CR1 and CR2, which apply compressive stress, can be located near the surface of the glass article 1000a, such as the first surface S1 and the second surface S2, and the tension region TR, which applies tensile stress, can be located within the glass article 1000a. The boundary between the compression regions CR1 and CR2 and the tension region TR can have a stress value of zero. The compressive stress in one of the compression regions CR1 and CR2 can have a stress value that varies depending on the location (e.g., depth from the surface). The tension region TR can also have a stress value that varies depending on the depth from the first surface S1 and the second surface S2.
[0117] In the glass article 1000a, the positions of the compression regions CR1 and CR2, the stress distribution in the compression regions CR1 and CR2, the compression energy in the compression regions CR1 and CR2, or the tension energy in the tension region TR may have a significant impact on the mechanical properties (e.g., surface strength) of the glass article 1000a.
[0118] Figure 6FIG. 1 is a diagram showing a glass product 1000a according to an embodiment (see FIG. Figure 5 ) is a graph of the stress distribution. Figure 6 In the graph, the x-axis represents the glass product 1000a (see Figure 5 ) in the thickness direction. Figure 6 In the present invention, the compressive stress has a positive value, while the tensile stress has a negative value. In this specification, the magnitude of the compressive stress / tensile stress refers to the magnitude of the absolute value without considering its sign.
[0119] Reference Figure 5 and Figure 6 , the glass article 1000a may include a first compression region CR1 extending (or expanding) from the first surface S1 to a first compression depth DOC1 and a second compression region CR2 extending (or expanding) from the second surface S2 to a second compression depth DOC2. The tension region TR may be positioned between the first compression depth DOC1 and the second compression depth DOC2. The overall stress distribution in the glass article 1000a may have a mutually symmetrical structure between the region on the first surface S1 and the region on the second surface S2 relative to the center in the direction of the thickness t. Although Figure 6 Not shown in FIG, but compression and tension zones may be positioned in a similar manner between opposing side surfaces of the glass article 1000a.
[0120] The first and second compression regions CR1 and CR2 can resist external impacts and thus prevent cracks from forming in the glass article 1000a and breakage of the glass article 1000a. The greater the maximum compressive stress CS1 in the first and second compression regions CR1 and CS2 in the second compression region CR2, the greater the strength of the glass article 1000a. Because external impacts are often transmitted through the surface of the glass article 1000a, it is desirable to have the maximum compressive stresses CS1 and CS2 on the surface of the glass article 1000a in terms of durability. The compressive stresses of the first and second compression regions CR1 and CR2 may be greatest on the surface and generally tend to decrease toward the interior of the first and second compression regions CR1 and CR2.
[0121] The first compression depth DOC1 and the second compression depth DOC2 can prevent cracks or grooves formed in the first surface S1 and the second surface S2 from propagating toward the tension region TR inside the glass article 1000a. As the first compression depth DOC1 and the second compression depth DOC2 increase, the propagation of cracks and the like can be prevented more effectively. Points corresponding to the first compression depth DOC1 and the second compression depth DOC2 may correspond to boundaries between the compression regions CR1 and CR2 and the tension region TR, and the stress values at the points become zero.
[0122] Throughout the glass article 1000a, the tensile stress in the tensile region TR can be balanced with the compressive stress in the compressive regions CR1 and CR2. In other words, the total compressive stress (e.g., compressive energy) in the glass article 1000a can be equal to the total tensile stress (e.g., tensile energy). The stress energy accumulated in a portion of the glass article 1000a having a uniform width in the thickness direction can be calculated as the integral value of the stress distribution. When the stress distribution in the glass article 1000a having a thickness t is represented by a function f(x), the following Formula 1 can be established.
[0123] [Formula 1]
[0124]
[0125] The greater the magnitude of the tensile stress in the glass article 1000a, the more violently the broken fragments will disperse if the glass article 1000a breaks, potentially causing breakage from within the glass article 1000a. The maximum tensile stress that satisfies the fragility standard of the glass article 1000a is not limited thereto and may satisfy the following formula 2.
[0126] [Formula 2]
[0127] CT1≤-38.7×ln(t)+48.2
[0128] In some embodiments, the maximum tensile stress CT1 may be in the range of about 85 MPa to about 100 MPa. It is desirable that the maximum tensile stress CT1 be at least about 75 MPa to improve mechanical properties such as strength. In embodiments, the maximum tensile stress CT1 may be in the range of about 75 MPa to about 85 MPa, but the present disclosure is not limited thereto.
[0129] The maximum tensile stress CT1 of the glass article 1000a may generally be at the center of the glass article 1000a in the thickness direction. For example, the maximum tensile stress CT1 of the glass article 1000a may be at a depth within a range of approximately 0.4t to approximately 0.6t. For example, the maximum tensile stress CT1 of the glass article 1000a may be at a depth within a range of approximately 0.45t to approximately 0.55t. For example, the maximum tensile stress CT1 of the glass article 1000a may be at a depth of approximately 0.5t.
[0130] To increase the strength of the glass article 1000a, it is desirable to have high compressive stress and compression depths DOC1 and DOC2. However, an increase in compressive energy leads to an increase in tensile energy, which in turn increases the maximum tensile stress CT1. It is desirable to adjust the stress profile to maintain high maximum compressive stresses CS1 and CS2 and large compression depths DOC1 and DOC2 while maintaining low compressive energy, thereby achieving both high strength and meeting fragility criteria. To this end, the glass article 1000a can be prepared from a glass composition containing specific components in specified amounts. Depending on the composition ratio of the components included in the glass composition, the prepared glass article 1000a can not only have high strength but also possess flexibility and physical properties suitable for foldable electronic devices.
[0131] According to an embodiment, the glass composition forming the glass article 1000a may include SiO2 in a range of about 60 mol% to about 70 mol%, Al2O3 in a range of about 5 mol% to about 15 mol%, Na2O in a range of about 5 mol% to about 15 mol%, Li2O in a range of about 5 mol% to about 15 mol%, and MgO in a range of about 0 mol% to about 5 mol%, relative to the total weight of the glass composition. According to an embodiment, the glass composition forming the glass article 1000a may not include ZrO2. According to an embodiment, the glass composition forming the glass article 1000a may not include K2O.
[0132] Each component of the glass composition is described in more detail below.
[0133] SiO2 can form the skeleton of the glass, increase chemical durability, and reduce the formation of cracks (indentations) on the glass surface. SiO2 can be a network-forming oxide that forms a glass network, and glass articles 1000a prepared using SiO2 can have a reduced coefficient of thermal expansion and improved mechanical strength. To achieve such an increase and decrease, the SiO2 content can be greater than or equal to about 60 mol%. To achieve sufficient meltability, the SiO2 content in the glass composition can be less than or equal to about 70 mol%.
[0134] Al2O3 can improve the breakability of glass. For example, Al2O3 can reduce the number of glass fragments in the event of glass breakage. Al2O3 can be an intermediate oxide that bonds to SiO2 to form a network structure. Al2O3 can improve ion exchange properties during chemical strengthening and can serve as an effective component for increasing surface compressive stress after strengthening. These functions are effectively performed when the Al2O3 content is at least about 5 mol%. To maintain the acid resistance and solubility of the glass, it is desirable that the Al2O3 content is less than or equal to about 15 mol%.
[0135] Na2O can form surface compressive stress through ion exchange and improve the solubility of the glass. Na2O can form ionic bonds with the oxygen in the SiO2 network structure, thereby generating non-bridging oxygen in the SiO2 network structure. The increase in non-bridging oxygen can improve the flexibility of the network structure, and the glass product 1000a can have physical properties suitable for foldable electronic devices. It is desirable that the Na2O content is at least about 5 mol% to effectively perform the above functions. In terms of acid resistance of the glass product 1000a, it is desirable that the Na2O content is less than or equal to about 15 mol%.
[0136] Similar to the above-mentioned Na2O, Li2O can form surface compressive stress through ion exchange and improve the solubility of glass. Li2O can form ionic bonds with oxygen in SiO2 that forms the network structure, thereby forming non-bridging oxygen in the SiO2 network structure. The increase in non-bridging oxygen can improve the flexibility and impact absorption of the network structure, and the glass product 1000a can have physical properties suitable for foldable electronic devices. It is desirable that the Li2O content is at least about 5 mol% to effectively perform the above functions. However, in terms of the heat resistance of the glass product 1000a, it is desirable that the Li2O content is less than or equal to about 15 mol%.
[0137] MgO improves the surface strength of glass and reduces the temperature at which glass forms. MgO is a network modifier oxide that reshapes the network structure of SiO2. MgO reduces the refractive index of glass and adjusts the thermal expansion coefficient and elastic modulus of glass. These functions are significantly enhanced when the MgO content is greater than 0 mol%. However, in terms of the meltability of the glass article 1000a, it is desirable that the MgO content in the glass article 1000a be less than or equal to approximately 5 mol%.
[0138] According to embodiments, the glass composition may satisfy the following Relationship 1 and / or Relationship 2.
[0139] [Equation 1]
[0140] 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0
[0141] In Relationship Formula 1, Al2O3, Na2O, and Li2O may be the contents (mol %) of the respective components.
[0142] According to an embodiment, the glass composition may satisfy the following Relationship 2.
[0143] [Equation 2]
[0144] 0.3≤Al2O3 / (the sum of Na2O, Li2O and MgO)≤1.0
[0145] In Relational Formula 2, Al2O3, Na2O, Li2O, and MgO may be the contents (mol %) of the respective components.
[0146] The network structure of a glass composition formed to include SiO2 and Al2O3 can be made flexible after the addition of Na2O and Li2O. Due to the addition of Na2O and Li2O, Na ions or Li ions can form ionic bonds with oxygen atoms between bonds forming the network structure (e.g., bonds between SiO2), thereby increasing the amount of non-bridging oxygen. The increase in non-bridging oxygen in the network structure can indicate that the bonds of the network structure are broken or opened, thereby allowing the network structure of the glass to gain flexibility. The glass composition can include Na2O in an amount of at least about 5 mol% and Li2O in an amount of at least about 5 mol% to provide the manufactured glass article 1000a with sufficient flexibility.
[0147] Because the glass composition includes a relatively excessive amount of Na2O and Li2O, the glass composition may have weak mechanical strength. To compensate for the fragility, the glass composition may include Al2O3, and according to the above equation 1, the ratio of Al2O3 to the sum of Na2O and Li2O may be adjusted to be within a range of 0.3 to 1.0, thereby increasing the mechanical strength of the network structure. According to embodiments, the glass composition may have a ratio (or R ratio) of Al2O3 to the sum of Na2O and Li2O within a range of 0.3 to 1.0.
[0148] As the ratio (R ratio) of Al2O3 to the sum of Na2O and Li2O included in the glass composition increases, Al2O3 may have a tetrahedral crystal structure including SiO2. In the network structure including SiO2, SiO2 may have a tetrahedral crystal structure (SiO4), and when the content of Na2O and Li2O increases compared to the content of Al2O3, Al2O3 may also have a tetrahedral crystal structure (AlO4). The content of non-bridging oxygen formed by the addition of Na2O and Li2O may be reduced, and the ion mobility of the glass composition may be increased. The increase in ion mobility may indicate an increase in the number of ions that move during chemical strengthening and the depth of ion penetration during the process of forming the glass article 1000a, and may improve the mechanical strength of the surface of the glass article 1000a. However, since flexibility decreases to the same extent as the mechanical strength of the glass composition increases, the ratio of Al2O3 to the sum of Na2O and Li2O (R ratio) can be formed to be in the range of about 0.3 to about 1.0 to achieve both sufficient mechanical strength and flexibility in an embodiment.
[0149] When the ratio of Al2O3 to the sum of Na2O and Li2O included in the glass composition (R ratio) is at least 0.3, the content of Na2O and Li2O can be increased, and the increased content of Na2O and Li2O can disrupt the network structure of SiO2, thereby increasing the interatomic distance in the network structure. As a result, a large amount of additional space can be formed in the network structure of SiO2, thereby improving impact absorption and flexibility.
[0150] In an embodiment, since the ratio (R ratio) of Al2O3 to the sum of Na2O and Li2O included in the glass composition has a value in the range of about 0.3 to about 1.0, the flexibility, strength against external impact, and impact absorption of the glass article 1000a may be improved.
[0151] The glass composition according to the embodiment may include Na2O and Li2O as materials that form non-bridging oxygen in the SiO2 network structure by forming ionic bonds with oxygen atoms in SiO2, but may not include K2O. During the process of forming the glass article 1000a, the strengthening process in which ion exchange occurs may be performed only once. During chemical strengthening, the glass composition may not include K2O to promote the migration of a large amount of Na ions or Li ions to the surface of the glass article 1000a. Because the glass composition does not include K2O, the glass composition according to the embodiment can achieve both a relatively high elastic modulus and relatively low brittleness.
[0152] In an embodiment, the glass composition may include approximately 65.3 mol% SiO2, approximately 8.9 mol% Al2O3, approximately 12.7 mol% Na2O, approximately 10.01 mol% Li2O, and approximately 3.0 mol% MgO, and the R ratio of the glass composition according to Relationship 1 may be approximately 0.39.
[0153] In addition to the above components, the glass composition may further include components such as SnO2, Y2O3, La2O3, Nb2O5, Ta2O5, and Gd2O3 according to embodiments. In embodiments, the glass composition may further include a small amount of Sb2O3, CeO2, and / or As2O3 as a fining agent.
[0154] The glass composition having the above composition can be formed into sheet glass in various ways. When the glass composition is formed into sheet glass, the glass composition may undergo additional processes to be manufactured into a glass product 1000a suitable for use in an electronic device 1. However, the present disclosure is not limited thereto. The glass composition may not be formed into sheet glass and may be directly formed into a glass product 1000a suitable for use in a product without requiring additional forming processes.
[0155] As described above, the glass article 1000a made from the glass composition according to the embodiment can have characteristics and physical properties suitable for foldable electronic devices. For example, the glass article 1000a can have the flexibility to be folded and unfolded, and can have the chemical properties and strength suitable for the cover window CW of the electronic device 1. When the glass article 1000a made from the glass composition according to the embodiment is folded, the formation of creases in the folded area can be prevented or reduced.
[0156] The impact resistance of the glass article 1000a may be related to various mechanical and chemical properties of the glass article 1000a. For example, the glass article 1000a may have physical properties such as thermal expansion coefficient, glass transition temperature, density, elastic modulus, Poisson's ratio, Vickers hardness, fracture toughness, and brittleness. According to embodiments, the glass article 1000a prepared from the above-described glass composition may satisfy the following properties.
[0157] [performance]
[0158] i) Thermal expansion coefficient (10 -7 K -1 ):85*10 -7 K -1 Up to 120*10 -7 K -1
[0159] ii) Glass transition temperature (T g ): 425℃ to 525℃
[0160] iii) Density: 2.38 g / cm 3 to 2.48g / cm 3
[0161] iv) Elastic modulus: 75 GPa to 85 GPa
[0162] v) Poisson’s ratio: 0.20 to 0.28
[0163] vi) Vickers hardness: 5.50 GPa to 6.50 GPa
[0164] vii) Fracture toughness: 0.75MPa*m 0.5 to 0.85MPa*m 0.5
[0165] viii) Brittleness: 4.9 μm -0.5 to 5.6μm -0.5
[0166] In an embodiment, the elastic modulus of the glass article 1000a may be in a range of about 80 GPa to about 85 GPa. In an embodiment, the elastic modulus of the glass article 1000a may be in a range of about 82 GPa to about 85 GPa.
[0167] In an embodiment, the brittleness of the glass article 1000a may be about 4.9 μm. -0.5 to about 5.4 μm -0.5 In an embodiment, the brittleness of the glass article 1000a may be about 4.9 μm. -0.5 to about 5.2μm -0.5 within the range.
[0168] Hereinafter, the embodiments are described in more detail based on the following preparation examples.
[0169] Preparation Example 1: Preparation of glass products
[0170] According to Table 1 below, a plurality of glass materials having various compositions were prepared and classified as Sample #1, Sample #2, Sample #3, Sample #4, Sample #5, Sample #6, Sample #7, Sample #8, and Sample #9, and glass articles were manufactured for each sample. The glass articles of each sample were manufactured to have a thickness of approximately 50 μm. Table 1 shows the composition of each sample.
[0171] The coefficient of thermal expansion (CTE), glass transition temperature (T g ), density (ρ), elastic modulus (E), Poisson's ratio (v), Vickers hardness (Hv), fracture toughness (K IC ), brittleness (B) and free volume performance indicators (FOM), and are organized in the following Table 2.
[0172] Here, the glass transition temperature (T g ) was determined using a differential thermal analysis (DTA) device. 5 g of each glass sample was prepared and heated to the glass transition temperature range at a rate of 10 K / min. The thermal expansion coefficient was determined using a thermomechanical analyzer (TMA) device. A 10×10×13 mm 3 The sample is heated to the glass transition temperature at a rate of 10 K / min.
[0173] Poisson's ratio (v) was determined using an elastic modulus tester. A 10×20×3 mm 3 The stress and strain of the specimen are measured.
[0174] Vickers hardness (Hv) and fracture toughness (K) were calculated using the following formulas 3 and 4 by applying a load of 4.9 N for 30 seconds using a Vickers hardness tester with a 19 μm diamond indenter. IC ).
[0175] [Formula 3]
[0176]
[0177] In formula 3, H V may be the Vickers hardness, F may be the load, and a may be the indentation length.
[0178] [Formula 4]
[0179]
[0180] In formula 4, K IC may be the fracture toughness, φ may be the constraint index of about 3, H V may be the Vickers hardness, K may be a constant of 3.2, c may be the crack length, and a may be the indentation length.
[0181] The brittleness (B) was calculated using the following Formula 5 by applying a load of 4.9 N for 30 seconds using a Vickers hardness tester.
[0182] [Formula 5]
[0183]
[0184] In Formula 5, B can be brittle and γ can be 2.39N. 1 / 4 / μm 1 / 2 where is a constant, P may be the indentation load, a may be the indentation depth, and C may be the crack length.
[0185] A Vickers hardness tester was used to measure the crack initiation load.
[0186] The FOM of the free volume is calculated using the following Equation 6, Equation 7, Equation 8, and Equation 9.
[0187] [Formula 6]
[0188] Free volume FOM = G 1C *(1 / B) 6 *E abs *(1 / T g )
[0189] In Formula 6, B may be brittle, and T g May be the glass transition temperature.
[0190] [Formula 7]
[0191] G1C =(K IC 2 (1-v 2 )) / E
[0192] In Formula 7, K IC may be the fracture toughness, v may be the Poisson's ratio, and E may be the elastic modulus.
[0193] [Formula 8]
[0194] E abs =σ 2 *(1-v) / E
[0195] In Formula 8, v may be Poisson's ratio, and E may be elastic modulus.
[0196] [Formula 9]
[0197] σ=(E*α*ρ 2 ) / (1-v)
[0198] In Formula 9, v may be Poisson's ratio, E may be elastic modulus, α may be thermal expansion coefficient, and ρ may be density.
[0199] [Table 1]
[0200]
[0201]
[0202] [Table 2]
[0203]
[0204] Referring to Tables 1 and 2, Samples #1 to #8 are glass articles prepared from glass compositions that include Na2O, Li2O, and KO and have a ratio of Al2O3 to the sum of Na2O, Li2O, and KO (or R ratio) of at least 3, and a ratio of Al2O3 to the sum of Na2O, Li2O, KO, and MgO (or R' ratio) of at least 3. Sample #9 is a glass article prepared from a glass composition that does not include KO and has a ratio of Al2O3 to the sum of Na2O and Li2O (or R ratio) of at least 3, and a ratio of Al2O3 to the sum of Na2O, Li2O, and MgO (or R' ratio) of at least 3.
[0205] The elastic modulus of sample #9 is 84 GPa, which is relatively higher than the elastic moduli of samples #1 to #8. The brittleness of sample #9 is 4.98 μm. -0.5, which is relatively lower than the brittleness of samples #1 to #8. In the case where the glass article has a relatively high elastic modulus, the glass article can be less deformed under the same pressure, and therefore, the degree of deformation when the glass article is folded in the folding area can be reduced. Generally, an increase in the elastic modulus tends to lead to higher brittleness, but in the case of sample #9 that does not include K2O, the elastic modulus is relatively high and the brittleness is low compared to samples #1 to #8 that include K2O. For example, in the case where the elastic modulus falls within the range of about 75 GPa to about 85 GPa and the brittleness is as low as about 4.9 μm -0.5 to about 5.6 μm -0.5 In the case of a glass article prepared from the glass composition according to the embodiment within the range of , deformation and / or crease formation when the glass article is folded in a folding area can be reduced or prevented, while also improving impact resistance.
[0206] The free volume FOM value of sample #9 is relatively larger than the free volume FOM values of samples #1 to #8. The free volume can be the space in which polymer chains can move freely, and as described with reference to Formulas 6 to 9, the free volume FOM value is determined based on brittleness, glass transition temperature, fracture toughness, Poisson's ratio, elastic modulus, thermal expansion coefficient, and density. As the free volume FOM value increases, the impact resistance of the glass article can be improved. When the numerical ranges of the above physical properties including brittleness, glass transition temperature, fracture toughness, Poisson's ratio, elastic modulus, thermal expansion coefficient, and density are met, and KO is not included as in sample #9, the impact resistance can be further improved (or increased) compared to the case where the numerical ranges of the above physical properties are not met or the case where KO is included.
[0207] According to the embodiment, a glass composition in which impact resistance is improved while reducing creases in the glass folding area, a glass product prepared from the glass composition, and an electronic device can be realized. However, the scope of the present disclosure is not limited by this effect.
[0208] The above description is an example of the technical features of the present disclosure, and those skilled in the art to which the present disclosure pertains will be able to make various modifications and variations. Therefore, the above-mentioned embodiments of the present disclosure may be implemented individually or in combination with each other.
[0209] Therefore, the embodiments disclosed in this disclosure are not intended to limit the technical spirit of this disclosure, but to describe the technical spirit of this disclosure, and the scope of the technical spirit of this disclosure is not limited by these embodiments. The scope of protection of this disclosure should be interpreted by the appended claims, and should be interpreted as all technical spirits within the scope of equivalents are included within the scope of this disclosure.
Claims
1. A glass product comprising: A glass composition comprising, relative to the total weight of the glass composition, SiO2 in a range of 60 mol% to 70 mol%, Al2O3 in a range of 5 mol% to 15 mol%, Na2O in a range of 5 mol% to 15 mol%, Li2O in a range of 5 mol% to 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to 5 mol%, Wherein, the glass composition satisfies the relation 1, and The thickness of the glass product is in the range of 20 μm to 100 μm, Relationship 1: 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0 In Relational Formula 1, Al2O3, Na2O, and Li2O represent the contents of the respective components in mol%.
2. The glass product according to claim 1, wherein The glass article has an elastic modulus in a range of 75 GPa to 85 GPa.
3. The glass product according to claim 1, wherein The brittleness of the glass product is 4.9 μm -0.5 to 5.6μm -0.5 within the range.
4. The glass product according to claim 1, wherein The thermal expansion coefficient of the glass product is 85*10 -7 K -1 Up to 120*10 -7 K -1 within the range.
5. The glass product according to claim 1, wherein The glass transition temperature of the glass article is in the range of 425°C to 525°C.
6. The glass product according to claim 1, wherein The density of the glass product is 2.38 g / cm 3 to 2.48g / cm 3 within the range.
7. The glass product according to claim 1, wherein The glass article has a Poisson's ratio in a range of 0.20 to 0.
28.
8. The glass product according to claim 1, wherein The glass article has a Vickers hardness in a range of 5.50 GPa to 6.50 GPa.
9. The glass product according to claim 1, wherein: The fracture toughness of the glass product is 0.75MPa*m 0.5 to 0.85MPa*m 0.5 within the range.
10. The glass product according to claim 1, wherein The glass article is foldable.
11. The glass product according to claim 1, wherein The glass composition also satisfies Relationship 2, Relationship 2: 0.3≤Al2O3 / (the sum of Na2O, Li2O and MgO)≤1.0 In Relational Formula 2, Al2O3, Na2O, Li2O, and MgO represent the contents of the respective components in mol%.
12. A glass composition comprising: SiO2 in a range of 60 mol% to 70 mol%, Al2O3 in a range of 5 mol% to 15 mol%, Na2O in a range of 5 mol% to 15 mol%, Li2O in a range of 5 mol% to 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to 5 mol%, relative to the total weight of the glass composition, Wherein, the glass composition satisfies the relation 1, Relationship 1: 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0 In Relational Formula 1, Al2O3, Na2O, and Li2O represent the contents of the respective components in mol%.
13. A display device comprising: A display panel, the display panel comprising a plurality of pixels; as well as a cover window, the cover window being arranged on the display panel, wherein the cover window includes, as a glass composition, SiO2 in a range of 60 mol% to 70 mol%, Al2O3 in a range of 5 mol% to 15 mol%, Na2O in a range of 5 mol% to 15 mol%, Li2O in a range of 5 mol% to 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to 5 mol%, relative to the total weight of the cover window; The glass composition satisfies the relationship 1, The thickness of the cover window is in the range of 20 μm to 100 μm, Relationship 1: 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0 In Relational Formula 1, Al2O3, Na2O, and Li2O represent the contents of the respective components in mol%.
14. The display device according to claim 13, wherein: The elastic modulus of the cover window is in the range of 75 GPa to 85 GPa.
15. The display device according to claim 13, wherein The brittleness of the cover window is 4.9 μm -0.5 to 5.6μm -0.5 within the range.
16. The display device according to claim 13, wherein The thermal expansion coefficient of the cover window is 85*10 -7 K -1 Up to 120*10 -7 K -1 within the range.
17. The display device according to claim 13, wherein: The cover window has a glass transition temperature in the range of 425°C to 525°C.
18. The display device according to claim 13, wherein The density of the cover window is 2.38g / cm 3 to 2.48g / cm 3 within the range.
19. The display device according to claim 13, wherein The Poisson's ratio of the cover window is in the range of 0.20 to 0.
28.
20. The display device according to claim 13, wherein The Vickers hardness of the cover window is in the range of 5.50 GPa to 6.50 GPa.
21. The display device according to claim 13, wherein The fracture toughness of the cover window is 0.75MPa*m 0.5 to 0.85MPa*m 0.5 within the range.
22. An electronic device comprising: A display panel, the display panel comprising a plurality of pixels; as well as a cover window, the cover window being arranged on the display panel, wherein the cover window includes, as a glass composition, SiO2 in a range of 60 mol% to 70 mol%, Al2O3 in a range of 5 mol% to 15 mol%, Na2O in a range of 5 mol% to 15 mol%, Li2O in a range of 5 mol% to 15 mol%, and MgO in an amount greater than 0 mol% and less than or equal to 5 mol%, relative to the total weight of the cover window; The glass composition satisfies the relationship 1, The thickness of the cover window is in the range of 20 μm to 100 μm, Relationship 1: 0.3≤Al2O3 / (the sum of Na2O and Li2O)≤1.0 In Relational Formula 1, Al2O3, Na2O, and Li2O represent the contents of the respective components in mol%.
23. The electronic device according to claim 22, comprising: Mobile phone, smart phone, tablet personal computer, mobile communication terminal, personal digital assistant, e-book terminal, portable multimedia player, navigation device, ultra-mobile personal computer, TV, laptop computer, monitor, billboard or IoT device.
Citation Information
Patent Citations
System and method of controlling vehicle
KR1020240039982A